EKC 2010 Proceedings of the EU-Korea Conference on Science and Technology - Han, Man-Wook.; Lee, Jehyun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Current research fields in science and technology were presented and discussed at the EKC2009, informing about the interests and directions of the scientists and engineers in EU countries and Korea. The Conference has emerged from the idea of bringing together EU and Korea to get to know each other better, especially in fields of science and technology.
Green Technology for Sustainability -- Science and Technology in Culture -- Physics and Nano Science -- Information and Communications Technology -- Bio Science and Health Technology.
Keywords: Engineering; Hydraulic engineering; Mechanical engineering; Telecommunication; Engineering; Mechanical Engineering; Engineering Fluid Dynamics; Communications Engineering, Networks